Estudo geomorfológico em cavernas de arenito da Amazônia paraense - Freire, Luciana Martins (2018)
In the Amazon region, which is rich in geomorphological features resulting from systemic interaction of nature elements stand out caves in sandstones. For example, there is the Speleological Province Altamira-Itaituba (Pará State), located in the geological domains of the sedimentary basin of the Amazon the contact zone of with the crystalline basement of the Xingu complex. In this sense, the proposed study, based on the geosystemic analysis of the landscape, presents an amplification of the studies on karst in non-carbonate rocks, contributing to speleological studies in Brazil. The geological structure of the caves of the Province presents notably in friable sandstone of Maecuru Formation belonging to Urupadi Group. Processes involving the formation of the caves are mainly associated with the mechanical action of water (hydric erosion), although water chemical action present fundamental role on intergranular dissolution.